2014
DOI: 10.1308/003588414x13824511650218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patient reported outcomes after Triathlon® and Kinemax Plus prostheses

Abstract: INTRODUCTIONThe Triathlon® (Stryker, Kalamazoo, MI, US) total knee replacement was designed to improve patient function and survivorship. The aim of this study was to determine whether the Triathlon® prosthesis produces better patient reported outcomes than a previous design by the same manufacturer, the Kinemax Plus.METHODSThe outcome of 233 knees of patients with a mean age of 68 years (range: 40–80 years) who received the Kinemax Plus prosthesis were compared with the outcomes of 220 knees of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Non-randomised studies comparing outcomes of the Triathlon TKA to other multi-radius designs including the Duracon [ 10 , 33 ] and the Kinemax Plus [ 14 ] have found in favour of the single-radius design in terms of pain relief [ 10 , 14 , 33 ], stability [ 10 ], degree of flexion [ 10 , 33 ], walking and stair climbing ability [ 10 ], Knee Society Scores [ 33 ] and knee-related quality of life [ 14 ]. Favourable Knee Society Scores have been reported by Harwin et al [ 23 ] in 2035 Triathlon TKAs in 1688 patients with 48-point improvements for pain and 22 for function at a mean of 21 months.…”
Section: Discussionmentioning
confidence: 99%
“…Non-randomised studies comparing outcomes of the Triathlon TKA to other multi-radius designs including the Duracon [ 10 , 33 ] and the Kinemax Plus [ 14 ] have found in favour of the single-radius design in terms of pain relief [ 10 , 14 , 33 ], stability [ 10 ], degree of flexion [ 10 , 33 ], walking and stair climbing ability [ 10 ], Knee Society Scores [ 33 ] and knee-related quality of life [ 14 ]. Favourable Knee Society Scores have been reported by Harwin et al [ 23 ] in 2035 Triathlon TKAs in 1688 patients with 48-point improvements for pain and 22 for function at a mean of 21 months.…”
Section: Discussionmentioning
confidence: 99%
“…Modern TKA femoral implants which mimic this geometry have demonstrated improved mid-flexion stability, preventing anterior movement of the femoral component during flexion [13]. The cohort studies published on these designs have demonstrated faster rehabilitation, reduction in anterior knee pain and improved range of motion over traditional knee designs [13,14,15]. However, there have also been studies which do not demonstrate an improvement in function over traditional knee systems [16,17,18].…”
Section: Introductionmentioning
confidence: 99%